Mixing Beyond Measure: Integrating Methods in a Hybrid Effectiveness–Implementation Study of Operating Room to Intensive Care Unit Handoffs. (April 2020) - Ross Perfetti, Angela; Peifer, Hannah; Massa, Scott; Di Taranti, Laura J.; Choudhary, Mahrukh; Collard, Meredith; George, Della; Wang, Cecilia; Beidas, Rinad; Barg, Frances K.; Lane-Fall, Meghan B.
During hospital handoffs, patient care and information are transferred between teams. Handoffs can expose patients to preventable harm related to lost information or misunderstandings between care teams. In the Handoffs and Transitions in Critical Care (HATRICC) project, we used a convergent mixed methods approach to design, implement, and evaluate a standardized process for handoffs between operating rooms and intensive care units. The value of this work to the field of mixed methods research is in illustrating how sustained, real-time integration of qualitative and quantitative methods contribute to an appropriate, acceptable, and ultimately more effective intervention. This approach allows for a nuanced understanding of implementation and effectiveness outcomes in a high-acuity clinical discipline largely characterized by quantitative approaches to improvement research.